The characteristics and associations between trait and state time perspective in adolescents with depression: a questionnaire and sandplay study - Ren,Hanlin; Zhang,Qing; Rong,Donghuan; Zhang,Yating; Ren,Yanzhen; Li,Xiaobao (PeerJ, 2024)
Background Time perspective is strongly associated with depression. However, the characteristics and associations between trait and state time perspective in adolescents with depression remain unknown. Methods A total of 211 adolescents with depression (mean age: 14.60 ± 1.69 years) and 215 healthy controls (mean age: 14.66 ± 1.73 years) were selected and assessed using the Chinese version of the Zimbardo Time Perspective Inventory to quantify their trait time perspective. Thirty adolescents were randomly selected from each group to create nine-grid sandplay productions to assess their state time perspective. Results (1) Regarding the trait time perspective, depressed adolescents scored significantly higher on past negative, present fatalistic, present impulsive, and deviation-balanced time perspective (p < 0.001) and significantly lower on past positive and future (p < 0.05) compared to the control group. (2) In terms of state time perspective, depressed adolescents showed a significantly higher number of squares related to past negative, present negative, and future negative in their nine-grid sandplay productions compared to the control group (p < 0.01).Conversely, they had significantly fewer squares associated with past positive, present positive, future positive than the control group (p < 0.05). (3) Past negative, present fatalistic, and deviation from balanced time perspective traits were negatively correlated with positive state time perspective and positively correlated with negative state time perspective. Past positive and future traits were positively correlated with positive state time perspective and negatively correlated with negative state time perspective. Conclusion Adolescents with depression are characterized by dwelling on the past, having a severely negative attitude toward the past, being pessimistic about the future, and having a tendency to blame fate or external forces for their problems. In the future, standardized methods for measuring state time perspective should be further explored, as well as the effectiveness of the nine-grid sandplay, for improving time perspective in patients with depression.
Keywords: Adolescence; Depression; Trait time perspective; State time perspective; Nine-grid sandplay therapy